Draft Fifth Five Year Plan 1974-1979 Volume-II (Detailed Sectoral Plans) Government of Nagaland - Planning Commission (Planning Commission, 1973)
The hilly State of Nagaland covers an area, of 16,488 sq. kms., of which approximately, 1,01 600 hectares are under cultivation. of this only 25,100 hectares are under permanent cultivation; the rest is under jhuming which is commonly known as "Shifting cultivation".
Government of Nagaland, Planning and Co-ordination Department